Day 1 Mon, March 21, 2016 2016
DOI: 10.2118/179792-ms
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Live Crude Oil Composition On Optimal Salinity of A Surfactant Formulation

Abstract: The objective of surfactant formulation design is to achieve ultra-low interfacial tension (IFT) with the oil in place in reservoir conditions. Several parameters have to be investigated, the presence of dissolved gas in crude oil can greatly impact the surfactant/brine/crude oil microemulsion phase behavior and omitting it may degrade the formulation efficiency. We propose an experimental investigation of optimal salinity evolution as a function of live oil compositions and conditions varying the pressure ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Very recently, Marliere et al have experimentally shown that the optimal salinity (and EACN by extension of Eq. 1) linearly decreases when increasing gas to oil ratio [23]. Thus, it appears promising to account for the volume fractions of gas and oil during any model development.…”
Section: Theoretical Sectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Very recently, Marliere et al have experimentally shown that the optimal salinity (and EACN by extension of Eq. 1) linearly decreases when increasing gas to oil ratio [23]. Thus, it appears promising to account for the volume fractions of gas and oil during any model development.…”
Section: Theoretical Sectionmentioning
confidence: 99%
“…In Equations (4)- (6), we assume that the dead crude oil can be represented by its EACN (EACNdo) determined experimentally as detailed in references [23,24]. The live crude oil EACN can be expressed as a function of EACNdo and gas EACN (EACNg) assuming a linear mixing rule based on volumetric fractions (Eq.…”
Section: Theoretical Sectionmentioning
confidence: 99%
See 3 more Smart Citations